Waterbird-Mediated Dispersal and Freshwater Biodiversity: General Insights From Bryozoans - Okamura, Beth; Hartikainen, Hanna; Trew, Jahcub (Frontiers in Ecology and Evolution, 2019)
Freshwater environments are fragmented and heterogeneous in space and time. Long term persistence thus necessitates at least occasional dispersal of aquatic organisms to locate suitable habitats. However, the insubstantial movements of many require zoochory –hitchhiking a ride with more mobile animals. We review evidence for zoochory of freshwater bryozoans, a group that provides an excellent model for addressing this issue. The feasibility of long distance transport by waterbirds of bryozoan propagules (statoblasts) is evaluated in relation to statoblast resistance to extreme conditions and waterbird gut retention times, flight durations and distances. We highlight genetic evidence for colonization following waterbird-mediated transport. The consequences of zoochory for biodiversity are manifold. Taxa that release statoblasts show lower levels of genetic differentiation, genetic divergence and haplotype diversity than those whose statoblasts are retained in situ (hence less available for zoochory). Zoochory may also disseminate pathogens and parasites when infected host stages are transported. Such co-dispersal may explain some disease distributions and is supported by viability of infected statoblasts. Zoochory can also be expected to influence local and regional population and community dynamics, food web structure and stability, and organismal distributions and abundances. Finally, zoochory may influence host-parasite coevolution and disease dynamics across the landscape with the benefits to parasites depending on their life history (e.g. simple vs. complex life cycles, generalists vs. specialists). Our synthesis highlights the complex ecological and evolutionary impacts of zoochory of freshwater organisms and raises questions for future research.